Study of collection accessions of the fiber flax gene pool according to the main agronomic characters in the conditions of the North-West of the Russian Federation - Aleksander D. Stepin; Michail N. Rysev; Tamara A. Ryseva; Svetlana V. Utkina; Nadezhda V. Romanova (Аграрная наука Евро-Северо-Востока)
Studies on the evaluation of 20 fiber flax accessions of Russian, Chinese, Japanese and Polish breeding from the collection of the Federal Research Center "All-Russian Institute of Plant Genetic Resources named after N. I. Vavilov" (VIR) were conducted in 2018-2020 in order to identify the sources of agronomic valuable characters that are adaptive to the conditions of the North-West of the Russian Federation. The HTC for the growing season in 2018 was 0.95, in 2019 – 1.53 and in 2020-1.1. Abiotic conditions had a greater influence on the formation of plant height (59.6 %), seed yield (60 %) and fiber content in plants (55.1 %), but the influence of the genotype on these indicators was also significant. The effect size of the genotype prevailed in the formation of fiber yield (67.2 %) and the duration of the growing season (52.8 %). The variability of characters was the greatest according to the seed yield (V = 6.7-33.9 %), disease resistance (V = 3.1-26.5 %); the lowest one was noted according to the duration of the growing season (V = 4.4-9.7 %). For the rest characters, it was at the level of up to 20 %. A valuable and plastic source material was identified for practical breeding aimed at creating new varieties with the following characters: early maturity – K-8680 (Russia), K-8782, K-8783 (Japan), which matured 3 days earlier than the Dobrynya standard and had a growing period of 67 days; productivity – K-8651, K-8760, K-8795, K-8797, K-8874, K-8877 (China), which significantly exceeded the fiber yield of the Dobrynya variety (241 g/m2) by 8-14 %. There were identified genotypes significantly exceeding the standard: according to the plant height (82 cm) ‒ K-8681 (Russia), K-8751, K-8794, K-8795, K-8754 (China) ‒ by 12-25 %; yield of flax straw (241 g/m2) – K-8681 (Russia), K-8751, K-8794, K-8795, K-8874, K-8880 (China) – by 25-40 %; seed yield (149 g/m2) ‒ K-8680 (Russia), K-8772 (Poland), K-8782 (Japan) – by 10-23 %; resistance to lodging (9 samples) and diseases (7 samples). Use of the identified gene sources in breeding practice should accelerate the creation of varieties that provide high and stable yields.